نفاذ وتنفيذ القرارات الإدارية بدولة الكويت : دراسة مقارنة مع ‏فرنسا ومصر - عجمي، محمد راشد (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2019)
The study aimed to define the concept of decision by reviewing definitions in jurisprudence and judiciary to distinguish administrative decisions and similar works related to it. This study highlighted the structures, characteristics and types of administrative decisions by studying the literal and terminological meaning of enforcement and execution concept. The study also analyzed the administrative decisions procedures in dealing with administration and individuals as well as mechanisms to inform and justify the administrative decisions before the determined period of execution. The study explored the implementations of enforcement and execution of administrative decisions in the laws and regulations of Kuwait, France and Egypt by examining administrative decisions in rules and regulation of these countries. The study used both the descriptive analytical approach and comparative and applied methodology. This study has found that both Kuwaiti and Egyptian legislators, like many legislators in other countries, do not define the administrative decision; they leave it to the discretionary power of both jurisprudence and judiciary, although the administrative judiciary of Kuwait and Egypt agree on a unified definition. The study highlighted there is a difference in jurisprudence and judiciary in determining the elements of the administrative decision and that some of them are unclear between the elements of the decision and the conditions of its validity due to the difference on defining the concept of administrative decision. It also shows similar stand among these countries regarding laws related with enforcement and execution of administrative decisions.